2009
DOI: 10.1016/j.neuron.2008.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Motor Control in a Drosophila Taste Circuit

Abstract: Tastes elicit innate behaviors critical for directing animals to ingest nutritious substances and reject toxic compounds, but the neural basis of these behaviors is not understood. Here, we use a neural silencing screen to identify neurons required for a simple Drosophila taste behavior, and characterize a neural population that controls a specific subprogram of this behavior. By silencing and activating subsets of the defined cell population, we identify the neurons involved in the taste behavior as a pair of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
580
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 509 publications
(595 citation statements)
references
References 47 publications
15
580
0
Order By: Relevance
“…We used the GRASP technique (GFP Reconstitution Across Synaptic Partners) (Feinberg et al, 2008;Gordon and Scott, 2009) to image contacts that cells make at the A/P compartment border. We expressed CD4:GFP 11 (transmembrane domain of mouse lymphocyte protein CD4 fused with a GFP fragment that includes the 11th strand of the 11-stranded photocenter) in the dpp domain (dpp-LexA lexO-CD4:GFP 11 ), and expressed CD4:GFP 1-10 (a fusion with a fragment that includes GFP photocenter strands 1-10) in the P compartment (hh-Gal4 UAS-CD4:GFP 1-10 ).…”
Section: Cell-cell Contacts At the A/p Compartment Bordermentioning
confidence: 99%
“…We used the GRASP technique (GFP Reconstitution Across Synaptic Partners) (Feinberg et al, 2008;Gordon and Scott, 2009) to image contacts that cells make at the A/P compartment border. We expressed CD4:GFP 11 (transmembrane domain of mouse lymphocyte protein CD4 fused with a GFP fragment that includes the 11th strand of the 11-stranded photocenter) in the dpp domain (dpp-LexA lexO-CD4:GFP 11 ), and expressed CD4:GFP 1-10 (a fusion with a fragment that includes GFP photocenter strands 1-10) in the P compartment (hh-Gal4 UAS-CD4:GFP 1-10 ).…”
Section: Cell-cell Contacts At the A/p Compartment Bordermentioning
confidence: 99%
“…Drosophila taste behavior and characterize a neural population that controls a specific subprogram of this behavior (Gordon and Scott, 2008).…”
Section: Data Inmentioning
confidence: 99%
“…The SOG region is widely regarded as the primary taste center in flies, and receives information from the sensory neurons and sends signals to control feeding movement after local circuit processing [31,54]. In recent years, although much progress has been made in identifying first-order sensory neurons and motor neurons controlling feeding movement, a direct connection between the two neuronal populations has not been reported, which suggests that there is at least a one-step relay mediated by interneurons in the SOG [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, although much progress has been made in identifying first-order sensory neurons and motor neurons controlling feeding movement, a direct connection between the two neuronal populations has not been reported, which suggests that there is at least a one-step relay mediated by interneurons in the SOG [31,32]. Recently one group reported that a single pair of NP883-Gal4 labeled neurons acts as interneurons and directs the feeding motor program [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation